The Symbiotic Future: How Artificial Intelligence is Transforming Electronic Health Record Systems - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into Electronic Health Record EHR systems is a significant advancement in modern digital health. EHRs, the cent...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care